2016
DOI: 10.1111/cei.12747
|View full text |Cite
|
Sign up to set email alerts
|

Dengue NS1 antigen contributes to disease severity by inducing interleukin (IL)-10 by monocytes

Abstract: 1These authors contributed equally to this study. SummaryBoth dengue NS1 antigen and serum interleukin (IL)-10 levels have been shown to associate with severe clinical disease in acute dengue infection, and IL-10 has also been shown to suppress dengue-specific T cell responses. Therefore, we proceeded to investigate the mechanisms by which dengue NS1 contributes to disease pathogenesis and if it is associated with altered IL-10 production. Serum IL-10 and dengue NS1 antigen levels were assessed serially in 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 47 publications
1
39
1
Order By: Relevance
“…IL-10 is an important anti-inflammatory cytokine and general suppressor of immune reactions, inhibiting IL-1, IL-6, IL-10 itself, IL-12, IL-18, CSF and TNFa, as well as inhibiting the synthesis of IL-2, IL-3, GM-CSF, TNFa and IFN-g (D' Andrea et al, 1993). IL-10 may contribute to disease severity through NS1-induced IL-10 production by monocytes, which in turn suppresses dengue-specific T cell responses (Adikari et al, 2016;Malavige et al, 2013b). Notably, data from animal studies suggest that NS1 activates immunological cascades in monocytes and macrophages leading to the pathologies observed in SD (Chen et al, 2015;Modhiran et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-10 is an important anti-inflammatory cytokine and general suppressor of immune reactions, inhibiting IL-1, IL-6, IL-10 itself, IL-12, IL-18, CSF and TNFa, as well as inhibiting the synthesis of IL-2, IL-3, GM-CSF, TNFa and IFN-g (D' Andrea et al, 1993). IL-10 may contribute to disease severity through NS1-induced IL-10 production by monocytes, which in turn suppresses dengue-specific T cell responses (Adikari et al, 2016;Malavige et al, 2013b). Notably, data from animal studies suggest that NS1 activates immunological cascades in monocytes and macrophages leading to the pathologies observed in SD (Chen et al, 2015;Modhiran et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Production of IL-10 may change according to the predominant cell type specific to the day of infection to regulate viral clearance immunopathology (reviewed by Tsai et al, 2013b) as different immune cells are invoked at different stages of dengue infections (Boonnak et al, 2008;Clyde et al, 2006). The timing of IL-10 production is dynamic and varies throughout the disease course, exemplified by IL-10 levels peaking around early defervescence in DHF patients, but less so in DF patients (Adikari et al, 2016;Butthep et al, 2012;Libraty et al, 2002a), suggesting that the biggest difference between DF and DHF patients may be observed around the day of early defervescence. Mechanistically, the intrinsic ADE of DENV infections may modulate the severity of dengue via increased IL-10 production and subsequent enhancement of the Suppressor of Cytokine Signalling (SOCS) system (Chareonsirisuthigul et al, 2007;Suhrbier & La Linn, 2003;Ubol et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively PAF may influence production of sPLA2 [35]. In our previous studies [9], significantly higher PAF levels were detected in patients with DHF and the dengue NS1 antigen was also shown to persist for a longer duration at higher levels [39,41]. Therefore, whether NS1 plays a role in inducing sPLA2 or PAF should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both DENV NS1 antigen and IL-10 serum levels were associated with severity in acute dengue infection, and IL-10 has suppressed dengue-specific T-cell responses [53]. Malavige and colleagues [54] demonstrated that NS1 is positively correlated with IL-10 production in monocytes, and induces its production, leading to severity. Therefore, our results showing an IL-10 reduction could be a consequence of N. brasiliensis effects in reducing NS1 and DENV production, acting simultaneously in an antiviral and immunomodulatory manner, and also improving the prognosis of infection.…”
Section: Discussionmentioning
confidence: 99%